2009
DOI: 10.1051/dst/2009046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host particle size on the modification of powder flow behaviours for lactose monohydrate following dry coating

Abstract: -Our previous work demonstrated that the powder flowability of a cohesive lactose sample can be improved substantially using a dry coating technique. Our study reported here aims to investigate the influence of host particle size on the modification of powder flowability following dry coating process. Four commercial lactose monohydrate powders with different particle sizes were coated by an intensive mechanical process or mixed using a conventional tumbling process, both with magnesium stearate. All four untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Dry powder coating has been extensively employed to improve various functionalities with a focus on enhancement of flowability, fluidisation, aerosolization and dispersion properties [11,12,14,16,17,23,24,43,44]. Inclusion of sub-micron fine guest particles on to the surface of micro-sized cohesive host particles resulted in the formation of surface asperities that reduce surface contact between cohesive particles thereby enhancing flowability, dispersibility or fluidisability [11,17,19,45,46].…”
Section: Functionality Characterisation (Characterisation Of Powder Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Dry powder coating has been extensively employed to improve various functionalities with a focus on enhancement of flowability, fluidisation, aerosolization and dispersion properties [11,12,14,16,17,23,24,43,44]. Inclusion of sub-micron fine guest particles on to the surface of micro-sized cohesive host particles resulted in the formation of surface asperities that reduce surface contact between cohesive particles thereby enhancing flowability, dispersibility or fluidisability [11,17,19,45,46].…”
Section: Functionality Characterisation (Characterisation Of Powder Bmentioning
confidence: 99%
“…Dry powder coating or hybrid mixing is a process where fine guest particles are adsorbed on to the surface of host particles under high impaction and shear forces [6][7][8][9][10][11][12][13][14][15] and Beach, L., PhD Thesis, New Jersey Institute of Technology, 2011]. The process generates forces of attraction between guest and host particles that are stronger than the weight of an individual fine guest particle resulting in deposition of the fine particles and synthesis of composite particles with improved functionalities or new properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that surface coverage of guest particles is dictated by particle characteristics including size and density [38]. Zhou et al [41,42] investigated the effect of host particle size on flow properties using lactose as a model host that was dry coated with magnesium stearate (MgSt) as a guest material using mechanofusion. The results indicated that the host particle size has a crucial effect on improving the flowability.…”
Section: Science Behind the Formation Of Functionalised Particles Usimentioning
confidence: 99%
“…Good flowability of dry powder is vital in various pharmaceutical operations like blending, die filling, tableting, capsule filling, re-suspending of powder in inhalers as well as cost reduction during handling, transportation and storage [42,55,[64][65][66][67]. Additionally, good flow property is necessary to achieve satisfactory fine-host interactive formulation properties in terms of metering, fluidisation, deagglomeration and dispersion [68].…”
Section: Enhanced Flowabilitymentioning
confidence: 99%